Gravitational wave probe of Planck-scale physics after inflation - Wei-Yu Hu; Kazunori Nakayama; Volodymyr Takhistov; Yong Tang (Physics Letters B, 2024)
Particle decays are always accompanied by the emission of graviton quanta of gravity through bremsstrahlung processes. However, the corresponding branching ratio is suppressed by the square of the ratio of particle's mass to the Planck scale. The resulting present abundance of gravitational waves (GWs), composed of gravitons, is analogously suppressed. We show that superheavy particles, as heavy as the Planck scale, can be naturally produced during the post-inflationary reheating stage in the early Universe and their decays yield dramatic amounts of GWs over broad frequency range. GW observations could hence directly probe Planck-scale physics, notoriously challenging to explore.